(untitled) (Global Journal of Science Frontier Research, 2014)
The world of finance works better through logistics and there are more to a risk measurement and hedging than being coherent. Thus, several predictable assumptions hast been made in other to make risk calculation and hedging tractable which both Value-at-risk (VaR) and Conditional tail expectation (CTE or CVAR) ignore useful information on target . The question is can the classical law of iterated logarithm(LIL)be centralized for risky and contingent hedging capacities? Here we find the imposition of the law of iterated logarithm (LIL) constraint unique and complete, hence continuous for the QUEST as it utilizes information in the whole distribution, curbs rate of returns on target, provides incentives for risk management and raises challenges of performances and cost.